Thermal dispersion effects on forced convection in a porous-saturated pipe. (June 2017) - Hooman, K.; Li, J.; Dahari, M.
Abstract: Thermal dispersion effects on fully developed forced convection inside a porous-saturated pipe are investigated. The pipe wall is assumed to be kept at a uniform and constant heat flux. Having the fully developed velocity field furnished by an arbitrary power series function, the energy equation is solved using asymptotic techniques for the limiting case when thermal conductivity, as a result of thermal dispersion, weakly changes with the Péclet number. A numerical solution, valid for the entire range of thermal dispersion conductivity, is also presented. This latter solution is presented to check the accuracy of the former. The two solutions are then cross-validated in the limits. Besides, results are found to be in good agreement with those previously reported in the literature.